Interdisciplinary partnerships for rural older adults' transitions of care. (14th September 2018) - Weil, Joyce; Milbrath, Gwyneth; Sharp, Teresa; McNeill, Jeanette; Gilbert, Elizabeth; Dunemn, Kathleen; Patterson, Marcia; Snyder, Audrey
Abstract : Purpose: Integrated transitions of care for rural older persons are key issues in policy and practice. Interdisciplinary partnerships are suggested as ways to improve rural-care transitions by blending complementary skills of disciplines to increase care's holistic nature. Yet, only multidisciplinary efforts are frequently used in practice and often lack synergy and collaboration. The purpose of this paper is to present a case of a partnership model using nursing, gerontology and public health integration to support rural-residing elders as a part of building an Adult-Gerontology Acute Care Nurse Practitioner program. Design/methodology/approach: This paper uses the Centre for Ageing Research and Development in Ireland/O'Sullivan framework to examine the creation of an interdisciplinary team. Two examples of interdisciplinary work are discussed. They are the creation of an interdisciplinary public health course and its team-based on-campus live simulations with a panel and site visit. Findings: With team-building successes and challenges, outcomes show the need for knowledge exchange among practitioners to enhance population-centered and person-centered care to improve health care services to older persons in rural areas. Practical implications: There is a need to educate providers about the importance of developing interdisciplinary partnerships. Educational programming illustrates ways to move team building through the interdisciplinary continuum. Dependent upon the needs of the community, other similarly integrated partnership models can be developed. Originality/value: Transitions of care work for older people tends to be multi- or cross-disciplinary. A model for interdisciplinary training of gerontological practitioners in rural and frontier settings broadens the scope of care and improves the health of the rural older persons served.